Teaching Vocabularies Through Idioms (Eurasian Scientific Herald, 2022)
It is undeniable that language plays the most important role in global communication. Because English is the universal language, it is essential to master it. Pronunciation, vocabulary, and grammar are the three most important aspects of learning English. Learning vocabulary entails expanding one's vocabulary. Word relations, multiple meanings, register, collocations, multi-word expressions, grammatical features of words, and cross-linguistic variances are the seven dimensions of knowing a word, according to scientists. If we wish to master vocabulary, we must learn every dimension. The most common issue that EFL students have is learning idiom as part of multi-word expressions. A multi-word phrase is made up of two or more words, and the meaning may often be deduced from the individual words alone. In this article discusses about teaching vocabularies through idioms and so on